Estudo químico e efeito gastroprotetor das infusões de Egletes viscosa (L.) Less - Portela, Benedito Yago Machado (2023)
Egletes viscosa (L.) Less. (Asteraceae) is an annual aromatic herb commonly found in northeastern Brazil, popularly known as “macela” or “macela-da-terra”, and traditionally prepared in infusions for the treatment of gastrointestinal disorders. This species has two chemotypes (A and B), differentiated based on the essential oil composition of the flower bud. Although there are previous studies on the gastroprotective effect of constituents isolated from E. viscosa, their infusions have not yet been investigated. Thus, the present study evaluated the gastroprotective and antidiarrheal effect of infusions of floral capitula of E. viscosa chemotype A (EVCA) or chemotype B (EVCB) in mice, in addition to describing the non-volatile chemical constituents. The infusions were prepared according to the traditional method of preparation and were analyzed using a metabolomics approach based on Ultra Performance Liquid Chromatography coupled with High Resolution Mass Spectrometry to determine their metabolic fingerprints and quantification of bioactive compounds. 24 compounds were identified, among which 7 are derived from phenolic acids, 3 are flavonoids and 14 are diterpenes. The quantification of bioactive compounds showed that EVCA has a higher amount of ternatin, tanabalin and centipedic than EVCB. Single oral administration of EVCA and EVCB, at a dose of 2000 mg/kg, did not cause acute toxicity during 14 days of observation in mice. Pre-treatment with EVCA (50, 100 and 200 mg/kg, p.o) significantly (p<0.05) reduced the area of ethanol-induced gastric lesions by 74, 70 and 70%, respectively, when compared to the vehicle group. While EVCB (50, 100 and 200 mg/kg, p.o.) reduced the gastric lesion area by 60, 59 and 62%. The evaluation of the gastroprotective mechanism of action of EVCA (100 mg/kg, p.o) and EVCB (100 mg/kg, p.o) in a model of gastric lesions induced by ethanol, in mice, involved antioxidant and anti-inflammatory action, with an increase in activity of catalase and superoxide dismutase enzymes, increase in reduced glutathione and nitrite levels and maintenance of gastric mucus, in addition to a reduction in malondialdehyde levels and myeloperoxidase activity. Pre-treatment with a cyclooxygenase (indomethacin) and nitric oxide synthase (L-NAME) inhibitor and with a potassium channel antagonist (glibenclamide) and transient receptor potential vanilloid type 1 (capsazepine), statistically inhibited (p<0.05) the gastroprotective effect of EVCA and EVCB in the model of ethanol-induced gastric injury. Furthermore, EVCA (100 mg/kg, p.o) and EVCB (100 mg/kg, p.o) were able to reduce secretion volume and total acidity and increase the pH of gastric contents in a pyloric ligation model in mice. Pre-treatment with EVCA (50, 100 and 200 mg/kg, p.o) significantly (p<0.05) reduced the area of gastric lesions induced by indomethacin by 82, 78 and 87%, respectively, when compared to the respective groups vehicle. While EVCB (50, 100 and 200 mg/kg, p.o) reduced the area of gastric lesion by 71, 75 and 94%. In the castor oil-induced diarrhea model, pretreatment with EVCA or EVCB (50, 100, and 200 mg/kg, p.o.) showed no statistical difference (p<0.05) compared to the vehicle group in any of the analyzed parameters. Therefore, both infusions of E. viscosa demonstrated gastroporteur potential mediated by antioxidant and antisecretory actions, including activation of TRPV1 receptors, stimulation of endogenous prostaglandins and nitric oxide, opening of KATP channels and maintenance of gastric mucus. Furthermore, the two chemotypes showed similar chemical compositions, including the presence of the biologically active constituents ternatin, tanabalin and centipedic acid.